Hubungan Kekerapan Pemberian Kolostrum dan Cara Lahir dengan Jumlah Koloni Bakteri Asam Laktat di Saluran Cerna Neonatus - Suci Rahmani Nurita; Mayetti Mayetti; Masrul Masrul (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
One of the biggest causes of infant mortality is an infectious diseases. Infectious diseases can be prevented through breastfeeding especially colostrum which is rich in nutrients, bioactive components, immunomodulatory factors and microbiota which play a role in the formation and development of the baby's immune system. Lactic Acid Bacteria (LAB) is one of the microbiota that plays an important role. This study aims to determine the relationship between frequency of colostrum and birth mode with the number of LAB colonies in the neonatal gastrointestinal tract. This study was observational with a cross sectional approach on 61 postpartum mothers and newborns at 2 hospitals (TK III Reksodiwiryo Hospital and DR. Rashidin Hospital) and 4 Independent Midwives Practice (BPM) in the Andalas, Ambacang and Belimbing Community Health Centre. Samples were obtained by consecutive sampling. The sample examination were done in the Microbiology Laboratory of Animal Product Technology, Faculty of Animal Science, Andalas University, Padang. Data analysis using T-Independent test and Pearson correlation test. The statistical test results showed no significant differences in the number of LAB colonies in the first 24 hours of birth in the neonatal gastrointestinal tract between those who were vaginally and C-section born (p = 0.912) and there was a significant relationship between the frequency of colostrum and the number of LAB colonies in the neonatal gastrointestinal tract on the 4th day births with a very strong correlation and a positive direction (p = 0,000; r = (+) 0.91). In this study it can be concluded that the number of LAB colonies in neonates born of vaginal and C-section not much different, this is due to colonization of LAB in the neonatal gastrointestinal tract can occur before birth. The more often colostrum is given, the more number of LAB colonies in the neonatal gastrointestinal tract.